A review of advancements in synthesis, manufacturing and properties of environment friendly biobased Polyfurfuryl Alcohol Resin and its Composites - D.C. Odiyi (22325356) (2023)
The quest for environmentally friendly and sustainable materials in the production of fibre reinforced composite materials has led to the use of biobased materials, which are easily accessible and renewable. Biomass-derived chemicals, their derivatives, and their applications have become increasingly prevalent in various industries and processes, greatly contributing to the goal of ecological sustainability. The biobased Polyfurfuryl Alcohol (PFA) resin is one of such polymeric materials that is gaining attention for composite applications due to its endearing Fire Smoke and Toxicity properties. Derived from agricultural by products such as sugar cane bagasse, it has been known for applications within the foundry, coating, and wood industries. However, there has been a growing interest in its use for fibre reinforced composite applications. For this reason, this work intends to provide a comprehensive review of the PFA resin in relationship to fibre reinforced composites applications. The work provides an in-depth discussion on the synthesis, curing process, manufacturing, and properties of the PFA resin as well as its composites. Other Information Published in: Composites Part B: Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compositesb.2023.111034